A systematic review of the association between rape myth acceptance and male-on-female sexual violence. (July 2018) - Yapp, Emma J.; Quayle, Ethel
Abstract: Rape myth acceptance is considered an established risk factor for male-on-female sexual violence, and is therefore the target of a number of primary prevention programmes. However, there is not a clear evidence base substantiating the role of rape myth acceptance in sexual violence, nor any reviews of recent literature. This review systematically searched relevant Psychology and Social Science databases in Autumn 2016, in order to collate cross-sectional and longitudinal research on the association between rape myth acceptance and self-reported sexual violence. The analysis established associations between these variables in all but one study (Warren, Swan, & Allen, 2015), and two longitudinal studies demonstrated that rape myth acceptance differentiates non-perpetrators from those who go on to exhibit sexual violence behaviours. These findings provide support for the targeting of rape myth acceptance in primary prevention strategies. However, a number of failings within this literature were also identified: instruments used to analyse rape myth acceptance were widely varied; the comprehensiveness of study reporting was universally flawed; measures were rarely taken to ensure participants were heterosexual men; and there remains a dearth of longitudinal evidence, as well as a lack of research outside of the United States. Future directions and other limitations are discussed. Highlights: Recent literature on the association between rape myth acceptance and sexual violence perpetration has not yet been reviewed. Rape myth acceptance is predictive of male-on-female sexual violence behaviours in 8 out of 9 included studies. Instruments used to measure rape myth acceptance and sexual violence are heterogeneous and scored in a variety of ways. Future directions are discussed.